1985
DOI: 10.1111/j.1440-1681.1985.tb00906.x
|View full text |Cite
|
Sign up to set email alerts
|

The EFFECT OF AGING ON Α‐ADRENOCEPTORS AND THEIR RESPONSES IN RABBITS

Abstract: The effects of age on alpha-adrenoceptor responses, sensitivity and number were studied in rabbits aged from 1 to 36 months. Three types of investigation were carried out: conscious animal studies, isolated tissue studies and radioligand binding studies. Specific [3H]-prazosin binding decreased with age in both spleen and heart suggesting that the number of alpha 1-receptors declined at least in the tissues studied. The specific binding of [3H]-clonidine to spleen membranes and [3H]-yohimbine to platelets was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…20 Interestingly, other animal studies also indicate that the a1-receptor density seems to decrease with increasing age, attenuating the responsiveness to a1-adrenergic agonists. [33][34][35][36] This is supported by a human study, in which infusion of the a1-adrenergic receptor agonist, phenylephrine, in young (mean age: 25.1 years) and old (mean age: 72.2 years) subjects at rest caused a less pronounced vasoconstriction response in the leg arteries of the older subjects. 37 Therefore, a higher a1-adrenergic receptor density would render peripheral arteries more sensitive to serum calcium.…”
Section: Discussionmentioning
confidence: 97%
“…20 Interestingly, other animal studies also indicate that the a1-receptor density seems to decrease with increasing age, attenuating the responsiveness to a1-adrenergic agonists. [33][34][35][36] This is supported by a human study, in which infusion of the a1-adrenergic receptor agonist, phenylephrine, in young (mean age: 25.1 years) and old (mean age: 72.2 years) subjects at rest caused a less pronounced vasoconstriction response in the leg arteries of the older subjects. 37 Therefore, a higher a1-adrenergic receptor density would render peripheral arteries more sensitive to serum calcium.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have demonstrated that vascular reactivity varies dramatically with postnatal developmental age. This observation holds for a variety of vascular beds, including cerebral (19,40,41), renal (18,28), femoral (36), and pulmonary (14,15,42) circulations. These data have been obtained in various species such as sheep (1,41), rat (12), pig (36,42), dog (37), rabbit (14,18), baboon (19,20), and human (5).…”
mentioning
confidence: 81%
“…However, they found no direct relation between the number of receptors and functional changes. 404 The reasons for the changes are not known but may be related to changes in hormone levels which occur before the animal reaches maturity. Alpha2-adrenoceptors labelled by [3H]clonidine have also been observed to decrease with age in the rabbit brain.402 However a decreased number of alpha,-adrenoceptors on platelets in newborn human infants has been reported and correlated with a diminished response of newborn platelets to adrenalinee405…”
Section: F Regulation Of Alpha-adrenoceptorsmentioning
confidence: 97%